Chosen Organizational Questions about Corrective Swimming and In-Water Corrective Exercises in Case of Scoliosis - Aleksander Wiażewicz; Maciej Zawadzki (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
In-water corrective exercises and corrective swimming are a very important element of prevention and correction of body posture defects. These occupancies are more frequently being used in modern treatment of these conditions. Advantageous influence of corrective exercises in water is predefined with specificity of water environment. The organization of corrective process is highly significant for successful final effects. The main aim of this review was to collect all organizational questions that may become useful for future instructors who want to carry the correction process effectively. The authors, based on literature review, personal knowledge and their experiences assembled most important organizational questions about swimming and in-water corrective exercises in case of multiply-curves scoliosis.